Mobile Cloud Computing Security and its Challenges (International Journal of Innovative Research in Engineering & Management, 2022)
Mobile cloud computing is a combination  of three types of technology. In which the first is mobile  computing, the second is cloud computing and the third is  wireless technology. Mobile cloud computing has become  a very important and advanced computing technology in  today’s time, But mobile devices are still affected by many  kinds of challenges or Issues. There is a problem of storage  in this, the problem of security, the problem of privacy  remains the problem of connectivity. Mobile cloud  computing is being used to overcome these problems, so it  is necessary that our mobile cloud computing is very  secure because at present work is being done in many  areas, such as in the field of education, in the field of  business, in the field of health, etc., With the help of mobile  devices. Due to which there are many security issues, till  through this paper, we have study what is in it. This type  of challenges can be seen and can be taken for research in  the future.
Keywords: Cloud computing; challenges; Security; Privacy